(untitled) (European Journal of Economics, Finance and Business Development, 2026)
This article examines the existing problems in enhancing the country’s investment attractiveness for attracting foreign investments and analyzes possible ways to overcome them. The study investigates the role of investment attractiveness in ensuring sustainable economic growth, industrial modernization, export expansion, and technological development. Particular attention is paid to institutional reforms, infrastructure development, macroeconomic stability, digital transformation, and regional investment disparities influencing foreign investment inflows into Uzbekistan. The research also identifies the main economic and organizational factors limiting investment attractiveness and evaluates practical mechanisms for improving the investment climate. Based on international experience and current economic reforms, scientific conclusions and practical recommendations aimed at increasing the efficiency of foreign investment attraction have been developed.